Prenatal diagnosis of criss-cross heart with congenitally corrected transposition of the great arteries – detection and fetal echocardiography monitoring with one-year postnatal follow-up - Murlewska, Julia; Kućmierz, Joanna; Witkowski, Sławomir; Żalińska, Agnieszka; Grzelak, Piotr; Respondek-Liberska, Maria (Prenatal Cardiology, 2022)
This paper presents an extremely rare and difficult case report of criss-cross heart (CCH) with a combination of congenitally corrected transposition of the great arteries (cc-TGA) of the fetal heart at 37 weeks of gestation. The impossibility of obtaining a proper 4-chamber view with opening of both the tricuspid and mitral valves in the same image as well as a parallel view of the great vessels confirmed later by neonatal volume-rendered computed tomography (CT) angiography were clues showing atrio-ventricular and ventriculo-arterial discordance. In addition to the heart defect, fetal echocardiography confirmed fetal well-being during subsequent exams and made it possible to plan vaginal delivery in a tertiary centre. Early cardiac surgery due to coexisting coarctation of the aorta (CoA) was performed on the 8th day and involved reconstruction of aortic arch and pulmonary artery banding. There were no clinical problems during the first year of postnatal life, despite abnormal intracardiac anatomy.